Hubungan Pengetahuan dan Sikap dengan Tindakan Mahasiswa Program Profesi Dokter Gigi RSGMP Universitas Andalas Terhadap Pengendalian Infeksi - Fitri Utami; Kuswardani Susari Putri; Hidayati Hidayati (Faculty of Dentistry Universitas Andalas, 2017)
Background: In dentistry, level of risk on cross infection can be said very high. This is due to the teeth treatment, the operator may have direct contact with saliva and patient’s blood. The implementation of standard precautions is very important in clinical practice because in addition to it must be obeyed, it can avoid the operator and the patient to the cross infection. The purpose: To determine the relationship between knowledge and attitudes with the practices toward infection control of clinical student in dentistry. Methods: This type research analytical observasional by cross sectional study approach. The number of respondents were 61 clinical student of dentistry. The sampling technique by simple random sampling. The data collection done by providing questionnaire concerning knowledge and attitudes to clinical student of dentistry and practice observations toward infection control. Statictical analysis use chi-square. Results: There is significant relationship between the knowledge with the practices toward infection control with p=0.0005 and significant relationship between the attitudes with the practices toward infection control with p=0.023. Conclusion: High knowledge and positive attitude will be followed by good practice of control infection.